Resistance inductors in control of coffee cercosporiose: analysis of genes related to defense - GUIMARÃES, SANDRA ELIZA; RESENDE, MÁRIO LÚCIO; DOS SANTOS, DEILA; MONTEIRO, ANA CRISTINA; VASCONCELOS, VICTOR AUGUSTO; JÚNIOR, MANOEL BATISTA (Coffee Science - ISSN 1984-3909, 2016)
The objective of this study was to evaluate the effect of resistance inducers, plant extract-based formulations and fungicide over the protection of coffee seedlings in controlling Cercospora coffeicola. In addition, the objective was to select alternative treatments that highlight in control of Cercospora leaf spot and study its effect as resistance inducer through the defense gene expression analysis. The treatments applied were: Greenforce CuCa, Greenforce KP, ET64-DT, which are plant extracts-based formulations (are under patent secrecy - PI 0603575-2), mineral fertilizer, acibenzolar-S-methyl (ASM) and, as control, the epoxiconazole + pyraclostrobin fungicide. We conducted weekly evaluations of incidence of cercosporiose to calculate the area under the curve of disease incidence progress (AUCDIP). After analysis of this experiment, the two best alternative treatments to evaluate the resistance-inducing potential of them were chosen. For this, a second experiment was carried out in order to analyze the expression of genes that are translated into the lipoxygenase, catalase, glutathione peroxidase and chitinase enzymes. The application of epoxiconazole + pyraclostrobin fungicide resulted in more effective control of the incidence of the disease, differing from the other treatments tested. The Greenforce Cuca and ASM, 0.05 g.L-1, products resulted in a reduction of AUCDIP of cercosporiose by 38 and 35%, respectively, differing from the other treatments. In the analysis of gene response expression to induce, it was observed that the highest expression of the genes encoding the lipoxygenase, catalase, glutathione peroxidase and chitinase enzymes occurred at 24 hours after application of ASM and 48 hours for Greenforce Cuca, no difference from one treatment to the other in these periods. Plants were sprayed with Greenforce Cuca showed a higher expression of the lipoxygenase gene at 72 hours after application of this product, differed from the ASM. With this work, we found that Greenforce Cuca and ASM products control Cercospora leaf spot through the induction of defense genes in coffee.